KOSTERMANSINDA RIFAI GENUS NOVUM HYPHOMYCETARUM - MIEN A. RIFAI (BRIN Publishing (Penerbit BRIN), 1968)
The conidial development of Sclerographium magnum Boedijn is described and illustrated; based on this species the new aleuriosporous genus Kostermansinda Rifai is proposed.